PERANCANGAN APLIKASI ALGORITMA AES RIJNDAEL PADA ENKRIPSI CITRA DIGITAL FILE JPEG 128 BIT - Dewi Cita Anggarini; Citra Kurniawan (Sinteks : Jurnal Teknik, 2017)
Human Problems Abuse Digital Image Data, Sender To Communicate That Sender Send Data To Recipient And want the data sent safe but in fact the data is susceptible to tapping on process of sending data so that itÂ  not up to recipient of data and fall into the hands of unauthorized people so can be misused. The way to maintain data security and confidentiality is by encryption and decryption techniques. This study aims to explain the implementation of jpeg rgb and grayscale file format in Aes Rijndael 128 bit Algorithm Application for encryption and decryption of digital image files. This research type is research & development (R & D). In this research, testing is done, that is the application feasibility test which includes media expert has 98% feasibility percentage and material expert has a feasibility percentage of 86%, concluded this application is very feasible. Conclusion if the Key used numbers with different pixel size and image capacity and resulted in different running times. The larger the pixel value of the image the time required is also the time and duration between encryption and decryption can be longer or even faster. If the length of the key pixel size and the same size of the image, does not affect the long running time, while if the pixel size is the same but the bigger the image is smaller then the running time is faster